1986
DOI: 10.2337/diab.35.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Islet Cell Composition During Development of Diabetes in Macaca nigra

Abstract: The islets of Langerhans in sections from the pancreas tail of Macaca nigra were stained by antiserum to insulin, glucagon, or somatostatin. The area of stained cells per total area of the islets was determined by a computerized photometric method. Insulin of the beta cells occupied 77% of the islet area in nondiabetic (ND) monkeys and decreased to 62% in monkeys in the earliest stages of metabolic deterioration, i.e., hormonally impaired (HI) monkeys. At the later stage of borderline diabetes (BD), monkeys ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Morphometric analysis of islets from hyperglycemic diabetic dogs revealed an abundance of immunoreactive glucagon per islet with an increase of 2-3-fold in glucagon area from the control (15-20% to 43-47%). This is in agreement with observations in other species (5)(6)(7)(8)(9)(19)(20)(21). However, the total glucagon content and concentration per pancreas did not change.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Morphometric analysis of islets from hyperglycemic diabetic dogs revealed an abundance of immunoreactive glucagon per islet with an increase of 2-3-fold in glucagon area from the control (15-20% to 43-47%). This is in agreement with observations in other species (5)(6)(7)(8)(9)(19)(20)(21). However, the total glucagon content and concentration per pancreas did not change.…”
Section: Discussionsupporting
confidence: 94%
“…The mean islet size and %IA in dog were close to the value observed in rat and human islets (19,20). Thus, our results are similar to the values that were obtained by the use of point-counting and linear-scanning procedures in other species (5)(6)(7)(8)(9)(19)(20)(21). Diabetes reduced the number of islets and the percent content of islets by 70% in the exocrine pancreas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This possibility is evidenced by studies of caloric restriction in monkeys (Cefalu et al 2004) and studies documenting lean elderly people as insulin sensitive as lean youths (Bryhni et al 2003). Islet amyloidosis has been reported in T2DM Macaca mulatta (de Koning et al 1993), Macaca nigra (Howard 1986), Macaca nemestrina (Ohagi et al 1991), Macaca fascicularis (Cromeens and Stephens 1985;O'Brien et al1996), and baboons (Hubbard et al 2002). We reported that the amyloid is immunoreactive for islet amyloid polypeptide (IAPP 1 ) and is generally associated with a marked reduction in insulin-immunoreactive ␤-cells (O'Brien et al 1996;Wagner et al 1996bWagner et al , 2001.…”
Section: Islet Amyloidosis Associated With T2dmmentioning
confidence: 94%
“…Diabetes has been reported in a number of Old World NHPs, including many macaque species (e.g., cynomolgus, rhesus, bonnet, Formosan rock, pig-tailed, and celebes macaques), African green monkeys, and baboons (Bodkin 2000;Clarkson et al 1985;Cromeens and Stephens 1985;de Koning et al 1993;Hansen and Bodkin 1986;Howard 1986;O'Brien et al 1996;Ohagi et al 1991;Tigno et al 2004;Wagner et al 1996a,b;Yasuda et al 1988). As in humans, most NHPs with diabetes have T2DM (Wagner et al 1996b(Wagner et al , 2001.…”
Section: Overview Of Diabetes In Old World Nhpsmentioning
confidence: 96%